Chaperone Mediated Autophagy Degrades TDP-43 Protein and Is Affected by TDP-43 Aggregation - Ormeño, Fernando; Hormazabal, Juan; Moreno, José; Riquelme, Felipe; Rios, Javiera; Criollo, Alfredo; Albornoz, Amelina; Alfaro, Iván E.; Budini, Mauricio (Frontiers in Molecular Neuroscience, 2020)
TDP-43 is a ribonuclear protein regulating many aspects of RNA metabolism. Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Lobar Degeneration (FTLD) are fatal neurodegenerative diseases with the presence of TDP-43 aggregates in neuronal cells. Chaperone Mediated Autophagy (CMA) is a lysosomal degradation pathway participating in the proteostasis of several cytosolic proteins including neurodegenerative associated proteins. In addition, protein oligomers or aggregates can affect the status of CMA. In this work, we studied the relationship between CMA and the physiological and pathological forms of TDP-43. First, we found that recombinant TDP-43 was specifically degraded by rat liver’s CMA+ lysosomes and that endogenous TDP-43 is localized in rat brain’s CMA+ lysosomes, indicating that TDP-43 can be a CMA substrate in vivo. Next, by using a previously reported TDP-43 aggregation model, we have shown that wild-type and an aggregate-prone form of TDP-43 are detected in CMA+ isolated lysosomes isolated from cell cultures. In addition, their protein levels increased in cells displaying CMA down-regulation, indicating that these two TDP-43 forms are CMA substrates in vitro. Finally, we observed that the aggregate-prone form of TDP-43 is able to interact with HSC70 and Lamp2A, as well as to up-regulate the levels of these molecular components of CMA. The latter was followed by an up-regulation of the CMA activity and lysosomal damage. Altogether our data shows that, i) TDP-43 is a CMA substrate, ii) CMA can contribute to control the physiological and pathological forms of TDP-43 and iii) TDP-43 aggregation can affect CMA performance. Overall, this work contributes to understanding how a dysregulation between CMA and TDP-43 would participate in neuropathological mechanisms associated with TDP-43 aggregation. Keywords: TARDBP, protein aggregation, cellular model, Chaperone Mediated Autophagy, lysosomal damage, Amyotrophic Lateral Sclerosis